Immune Surveillance Plays a Role in Locally Aggressive Giant Cell Lesions of Bone. Issue 12 (December 2017) - Al‐Sukaini, Ahmad; Hornicek, Francis J.; Peacock, Zachary S.; Kaban, Leonard B.; Ferrone, Soldano; Schwab, Joseph H.
Abstract : Background : Giant cell lesions are locally aggressive intraosseous neoplasms with capacity to metastasize. The role of immune surveillance in the pathophysiology of giant cell lesions is poorly understood, and understanding what role the immune system plays in giant cell lesions may lead to the development of more effective treatment. The aim of this study was to explore the role of immune surveillance in giant cell lesions by examining the expression of the HLA class I and class II antigens and tumor infiltrating lymphocytes. In addition, we examined the role of the immune modulating surface antigen B7‐H3, which belongs to the B7 superfamily, a group of molecules that modulates T‐cell responses. Questions/Purposes : (1) Is an immune response elicited by giant cell lesions? (2) Do clinically relevant human leukocyte antigen (HLA) defects exist in giant cell lesions? (3) Is B7‐H3 a clinically relevant immune modulator? Methods : The study sample was derived from the population of patients presenting to the Massachusetts General Hospital for evaluation and management of giant cell lesions from 1993 to 2008. We included patients with histologically confirmed giant cell lesions with a minimum followup of 6 months. Patients with systemic diseases (n = 4 [3%]), syndromes associated with giant cell lesions (n = 4 [3%]), and those without sufficient followup (n = 26 [19%]), inadequate records (n = 7 [5%]), or inadequate tissue available (n = 2 [1%]) were excluded. Tissue microarray, containing 288 tissue cores for 93 patients, was carefully constructed. This contained tissue from 45 patients with maxillofacial lesions, 38 with aggressive and seven with nonaggressive lesions, and 48 patients with axial and appendicular lesions, 30 with aggressive lesions and 18 with nonaggressive lesions. The population mean age was 28 ± 12 years and the duration of followup was 4 ± 3 years. The tissue microarray was immunohistochemically stained with monoclonal antibodies specific for HLA classes I and II and B7‐H3 antigens and analyzed for tumor infiltrating lymphocytes. Antigen expression was examined in multinucleated giant cells and mononuclear stromal cells. The results were correlated with local invasion and tumor aggressiveness, which is based on accepted staging criteria. Results : Tumor infiltrating lymphocytes were detected in all the tumors. The mean number of CD8+ T cell infiltration was lower in aggressive tumors (median, 4.8; interquartile range [IQR], 0.4‐13.4), when compared with nonaggressive tumors (median, 15.8; IQR, 4.3‐46.3; p = 0.007). HLA class I antigens were highly expressed by multinucleated giant cells in all tumors, but were lightly expressed on mononuclear stromal cells in 53% (45 of 84) to 73% (56 of 77) of tumors. HLA class I antigen low expression in mononuclear stromal cells was associated with tumor aggressiveness (odds ratio [OR], 4.3; p = 0.005). Low HLA class I expression combined with low CD8+ T cell infiltration was most highly associated with tumor aggressiveness (OR, 7.81; p = 0.011). B7‐H3 antigen was expressed in 36.9% mononuclear stroma cells and also was associated with local tumor invasion (OR, 1.36; p < 0.001). Similarly, giant cell lesions with high B7‐H3 expression and low CD8+ tumor infiltrating lymphocytes were associated with increased tumor aggressiveness (OR, 8.89; p = 0.0491). Conclusions : Locally aggressive giant cell lesions are associated with low HLA class 1 antigen expression, low CD8+T cell infiltration, and high expression of the immune modulator B7‐H3. Clinical Relevance : Failure of immune surveillance implies that there may be an opportunity to target aspects of the immune surveillance machinery to treat giant cell lesions.